2019
DOI: 10.3390/plants8120555
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Antifungal Variability of Several Accessions of Azadirachta indica A. Juss. from Six Locations Across the Colombian Caribbean Coast: Identification of Antifungal Azadirone Limonoids

Abstract: Plant materials (i.e., leaves, fruits, and seeds) from 40 trees of Azadirachta indica A. Juss. were collected from six different locations across the Colombian Caribbean coast. Eighty-four ethanolic extracts were prepared and the total limonoid contents (TLiC) and the antifungal activity against Fusarium oxysporum conidia were measured. Their chemical profiles were also recorded via liquid chromatography-electrospray ionization interface-mass spectrometry (LC-ESI-MS) analysis and the top-ranked features were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…First, we identified the seven most abundant constitutive alkaloids in D. stramonium : four tropane alkaloids (atropine, scopolamine, 3‐hydroxy‐6‐tigloyloxytropane, and anisodamine; De‐la‐Cruz et al. 2020), one alkaloid derived from the phenylalanine biosynthesis (phenylacetaldehyde), one pyrrolizidine alkaloid (pyrroline), and one triterpenoid of unknown name but of similar structure and molecular weight to azadirone triterpenoid (Álvarez‐Caballero and Coy‐Barrera 2019) (Supporting Information S2). Each alkaloid was searched and integrated (peak integration) individually in each chromatogram of each plant.…”
Section: Methodsmentioning
confidence: 99%
“…First, we identified the seven most abundant constitutive alkaloids in D. stramonium : four tropane alkaloids (atropine, scopolamine, 3‐hydroxy‐6‐tigloyloxytropane, and anisodamine; De‐la‐Cruz et al. 2020), one alkaloid derived from the phenylalanine biosynthesis (phenylacetaldehyde), one pyrrolizidine alkaloid (pyrroline), and one triterpenoid of unknown name but of similar structure and molecular weight to azadirone triterpenoid (Álvarez‐Caballero and Coy‐Barrera 2019) (Supporting Information S2). Each alkaloid was searched and integrated (peak integration) individually in each chromatogram of each plant.…”
Section: Methodsmentioning
confidence: 99%
“…Nimonol was the best inhibitor; of which inhibition against F. oxysporum conidia germination was observed at IC 50 of 1.48 µM. Alvarez-Caballero and Coy-Barrera (2019) also demonstrated that the presence of a 14, 15-epoxy group and the saturation at 1, 2-olefilic positions in the structure of azadirone-type limonoids led to a diminished effect on fungal conidia germination [11]. In our study, 1, 3, 4, and 5 were isolated and identified as azadirone-type limonoids.…”
Section: Discussionmentioning
confidence: 93%
“…Over the years, the well-known limonoids and neem extracts were documented as successful examples of botanical insecticides commercialized. Based on the record of known safety, mode of action, and interaction of the limonoid active ingredients, the chemical class is expected to repurpose or use widely for controlling the phytopathogens in organic agriculture [9][10][11][12][13]. However, to our best knowledge, there are very few studies on the activity of Meliaceous limonoids against phytopathogenic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…In Vitro Bioassay Against F Oxysporum F oxysporum LQB-03, a virulent isolate obtained from wilting Physalis peruviana plants, was used as the assessed phytopathogen. 43 This isolate had been preserved on Whatman paper # 1 at −20 °C and further reactivated in potato dextrose agar (PDA) to be used in the present antifungal assays. The in vitro antifungal activity against F oxysporum was evaluated by inhibiting mycelial growth (12-well plate amended semisolid medium assay).…”
Section: Discussionmentioning
confidence: 99%